Comparison of Cut Out Transmission Variations on a 10x10 cm2 Applicator for Linac Electron Beam - Oktafianingrum, Alisya; Stevenly, Robert Janssen; Wardani, Pratiwi Sri; Putri, Erlinda Ratnasari (Jurnal Fisika Flux: Jurnal Ilmiah Fisika FMIPA Universitas Lambung Mangkurat, 2024)
Radiotherapy has provisions for providing radiation doses for patient therapy, as giving the minimum possible dose to healthy tissue and giving the maximum possible dose to cancer. The aim of this research is to compare the electron beam output with measurements of cut out transmission variations (using a built-in block, without using a block, and using a cerrobend block). This research used a 10x10 cm2 applicator which was attached to the Linac. The blocks were installed and the absorbed dose was measured using water phantom and Markus ionization detektor. Besides that, absorbed dose was also measured without blok. The energy used in this study was 12 MeV and the a mount of radiation dose from Linac was 100 MU. Measurement results using a built-in block (lead) of 100 cGy, a cerrobend block of 100 cGy. Measurements without using a block were 102 cGy. This measurement has a comparison in the results that get low and high deviation values. Measurements using lead blocks and cerrobends are 0%, while measurements without blocks have a deviation value of 2%. These three measurements are still within the IAEA 398 TRS standard tolerance limit, i.e, ± 2%.